Cadmium and Lead Decrease Cell–Cell Aggregation and Increase Migration and Invasion in Renca Mouse Renal Cell Carcinoma Cells - Akin, Ryan (Int J Mol Sci, 2019)
Metastatic renal cell carcinoma (RCC) remains an important clinical issue; the 5-year survival rate of patients with metastasis is approximately 12%, while it is 93% in those with localized disease. There is evidence that blood cadmium and lead levels are elevated in RCC. The current studies were designed to assess the impact of cadmium and lead on the progression of RCC. The disruption of homotypic cell–cell adhesion is an essential step in epithelial-to-mesenchymal transition and tumor metastasis. Therefore, we examined the impact of cadmium and lead on the cadherin/catenin complex in Renca cells—a mouse RCC cell line. Lead, but not cadmium, induced a concentration-dependent loss of E-cadherin, while cadmium, but not lead, increased p120-catenin expression, specifically isoform 1 expression. Lead also induced a substantial increase in matrix metalloproteinase-9 levels. Both cadmium and lead significantly decreased the number of Renca cell aggregates, consistent with the disruption of the cadherin/catenin complex. Both metals enhanced wound healing in a scratch assay, and increased cell migration and invasion. These data suggest that cadmium and lead promote RCC progression.